Desertification network for NGOs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Desertification Action Centre of UNEP (United Nations Environment Programme) has just established a network of NGOs to help in its fight against deforestation and desertification in Asia, including the Pacific islands. An electronic...